Evaluation of Motor Sensory Blockade and Duration of Analgesia in Dexmedetomidine and Dexamethasone as Adjuvant to Bupivacaine - Ravi Gurbani; Rashim Vachhani (Academia Anesthesiologica International, 2019)
Background: The studies are scant about the analgesic efficacy of the Dexamethasone and dexmedetomidine. Hence this study was taken up to assess the efficacy of Dexamethasone as an analgesic especially for upper limb surgeries.Subjects and Methods: 200 patients belonging to ASAI and ASAII were included in the study scheduled for upper limb surgeries after taking informed consent. These patients were divided in to two groups having 50 patients in each group. Group A received 20ml of 2% lignocaine with adrenaline plus 18ml of 0.5% bupivacaine plus 50?g of dexmedetomidine and group B received 20ml of 2% lignocaine with adrenaline plus 18ml of 0.5% bupivacaine plus 8mg of dexamethasone. Onset of sensory and motor block, duration of block, quality of intraoperative analgesia and duration of analgesia were recorded.Results: Our study revealed similar onset of sensory block in group A and B. Group A showed early onset and longer duration of motor block compared to group B. Intraoperative haemodynamics were similar in both groups.Conclusion: Our study concludes that using dexmedetomidine as adjuvant prolongs the duration of block and postoperative analgesia compared to dexamethasone with minimal or negligible adverse events.